PEMAHAMAN DAN IMPLEMENTASI ICT PADA GURU TK YANG TELAH MEMILIKI KOMPUTER DALAM MEMBUAT PERANGKAT PEMBELAJARAN DI KABUPATEN TEGAL DAN BREBES - Astuti, Marcilia Dwi (Jurusan PGPAUD FIP UNNES, 2014)
The use of Information and Communication Technology ( ICT ) in learning is very important in education, especially implemented early childhood education. Kindergarten teacher comprehension ability in the use of ICT is need for mastery of ICT strongly support the learning activities in each school . The purpose of this study to determine comprehension of Tegal and Brebes kindergarten teachers in the district and Brebes in the use of ICT, to know the implementation of the use of ICT to make learning devices carried by kindergarten teachers in Tegal regency and Brebes, and to identify barriers faced by teachers and kindergarten in Tegal Brebes in understanding and implementing the use of ICT to make learning device. The method in this research is descriptive quantitative survey approach. The population used in this study is a kindergarten teacher ( S1 ) and kindergarten institutions that already have a computer/laptop in Tegal regency and Brebes totaling 89 people from 22 institutions. The results showed that kindergarten teachers in Tegal regency and Brebes are known to have understood the use of ICT by the total percentage of 74.8 % understood categories. As for the results of the implementation of the use of ICT to make learning device with a total percentage of 75.9 % category often ( once a week ). Barriers faced by kindergarten teachers in Tegal regency and Brebes in understanding and implementing the use of ICT is the internal resistance of a teacher lies in memory and in terms of time, while the external obstacle lies in the facility computer / laptop that is still lacking. It can be concluded that the kindergarten teachers in the district comprehension of Tegal and Brebes in the use of ICT to communicate, develop themselves, to the benefit of the delivery of an educational activity has been well understood in accordance with professional and pedagogical competence. As for implementation, kindergarten teachers have to apply and utilize ICT to communicate, for the sake of organizing educational activities in accordance with good professional and pedagogical competence.Keywords : Deaf Children; Application of Language Development; Language Development